2019
DOI: 10.1007/s00442-019-04571-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon export is facilitated by sea urchins transforming kelp detritus

Abstract: With the increasing imperative for societies to act to curb climate change by increasing carbon stores and sinks, it has become critical to understand how organic carbon is produced, released, transformed, transported, and sequestered within and across ecosystems. In freshwater and open-ocean systems, shredders play a significant and well-known role in transforming and mobilising carbon, but their role in the carbon cycle of coastal ecosystems is largely unknown. Marine plants such as kelps produce vast amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Also, it could be because the material, even as detritus, can remain viable and photosynthetically active for extended periods in shallow subtidal areas with su cient light to maintain net photosynthesis 50 . Although critical information about export of this detrital material is still lacking in many regions 11 , our ndings show that kelp detritus has long residence times in the coastal zone, and therefore high potential to be transported to deeper regions 36,47 . This is consistent with evidence that a substantial amount of kelp reaches deep marine sinks where it can be sequestered in the long-term 11,32,51 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Also, it could be because the material, even as detritus, can remain viable and photosynthetically active for extended periods in shallow subtidal areas with su cient light to maintain net photosynthesis 50 . Although critical information about export of this detrital material is still lacking in many regions 11 , our ndings show that kelp detritus has long residence times in the coastal zone, and therefore high potential to be transported to deeper regions 36,47 . This is consistent with evidence that a substantial amount of kelp reaches deep marine sinks where it can be sequestered in the long-term 11,32,51 .…”
Section: Discussionmentioning
confidence: 77%
“…Each cage was tethered with cable ties to a weight on the sea oor at ~8-m depth. In order to accurately quantify the impact of ocean climate on decomposition, we selected this cage size to exclude grazing by large herbivores in our experiments, which can drive localized increases in the turnover, size, and availability of kelp detritus in some areas 36 and could overwhelm measures of turnover in areas where they were locally abundant. All kelp pieces were kept damp after collection, stored in a dark cooler and deployed within 24 hours of collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea urchins Strongylocentrotus spp. are known as active opportunistic grazers with the preference for macroalgae (Briscoe & Sebens, 1988; Evseeva, 2016; Filbee‐Dexter et al, 2020; Kuznetsov, 1946; Paar et al, 2019). Studies of the metabolism and demography of S. droebachiensis on the Murman coast led Propp (1977) to the conclusion that the food demands of sea urchins cannot be fulfilled by kelp production and has to be compensated by consuming fucoids and other algal material transported from the intertidal to the subtidal zone.…”
Section: Discussionmentioning
confidence: 99%
“…In some places, such regime shifts have been accompanied by a hysteresis effect of approximately one order of magnitude in urchin biomass, which has maintained barrens between the critical threshold of overgrazing and recovery (Ling et al, 2015). Sea urchin barrens can persist in the absence of seaweeds because surviving urchins can shift their food source to less nutritious microalga or invertebrates growing on the open rocky substrates (Ling & Johnson, 2009), or acquire floating algae, algae fragments and detritus via their spines and tube feet (Campbell et al, 1973;Russo, 1980;Filbee-Dexter et al, 2020). Previous research has shown that predation pressure by sea urchins with high population densities continues to exceed seagrass growth and prevent recovery of kelp forest (Sivertsen 1997;Filbee-Dexter & Scheibling, 2014), and that the absence of sea urchin predators by fisheries prevents seaweed recovery (Johnson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%